Numerical simulation of the behaviour of a moored ship inside an open coast harbour - Pinheiro, L. (2013)
Sea waves inside harbors can affect scheduled port operations. Hence it is important to correctly predict and characterize the wave field inside ports and to describe the movements of the ship and forces acting upon it. A classical approach is to assume that shipwave interaction is linear, [1]. Then it is possible to decompose it in the so-called radiation and diffraction problems. Numerical models that solve such problems have been developed and used by the offshore industry for quite a while, [2], to study the interaction of sea-waves with floating objects. However, these models cannot be used to solve the diffraction problem of ships inside harbor basins where nearby reflecting boundaries and shallow depths create very complex nonlinear wave fields. A new set of procedures using coupled models is proposed in this work. First, a Boussinesqtype finite element wave propagation model is used to determine the wave field in the numerical domain containing the harbor. Then the velocity potentials are evaluated at the ship’s hull and finally, the Haskind relations [3] are used to determine the wave forces on the ship along the six modes of motion (heave, sway, surge, roll, pitch and yaw). This new methodology for the evaluation of diffraction forces on a ship inside a harbor basin is presented and tested in this paper. Movements of the moored ship and tensions on the mooring system are obtained using a numerical solver for the motion equations of a moored ship. An application to an open coast harbor is presented.